UTILIZATION OF INSTAGRAM SHOPPING FEATURES AS A MEDIA FOR MARKETING COMMUNICATION FOR ONLINE STORES CARL AND CLAIRE - Siti Meisyaroh; Amelia Katherine Surya (Jurnal Komunikasi dan Bisnis, 2022)
The extraordinary growth and development of online business has led to intense business competition. Instagram is one of the social media that is here to offer solutions for business owners and their potential customers by issuing special shopping features. One of the online stores that utilizes the Instagram Shopping feature as a marketing communication media is Carl & Claire. In this study, researcher tried to discover the use of the Instagram Shopping feature as a marketing communication medium for Carl & Claire's online store and also discover the advantages and disadvantages using the 4P marketing mix concept. The 4 concepts included in the 4P marketing mix are: Product, Price, Place, and Promotion. The research method used by the researcher in this study is a qualitative descriptive research method. The data in this study were obtained from primary data and secondary data. The data collection technique that the researcher used was observation, documentation, and interviews with 2 informants, namely Mrs. Nouva Puspita as the CEO & Founder of Carl & Claire and Ms. Kezia Marika Puteri as the Junior Brand Manager of Carl & Claire.